Augmentation with Amisulpride for Schizophrenic Patients Non-Responsive to Risperidone Monotherapy - Toledo-Romero, F.; Molina, J. D.; López-Rodríguez, E.; Amorin-Díaz, M.; Muñoz Algar, M. J.; Aparicio-Castro, E. (Pharmacopsychiatry, 2015)
Introduction: The combination of antipsychotic drugs is a therapeutic resource in clinical practice. This study aimed to evaluate the efficacy and security of adding amisulpride in patients who at least partially responded to risperidone.Methods: A 3-month, open, observational study was undertaken to evaluate the effectiveness of adding amisulpride in subjects who scored at least 25 on the brief psychiatric rating scale (BPRS) after risperidone monotherapy. Patients were evaluated with BPRS, the Clinical Global Impressions Severity of Illness scale (CGI-S) and the Udvalg for Kliniske Undersøgelser Side Effect Rating Scale (UKU) at baseline, 1 and 3 months.Results: Coadjuvant treatment with amisulpride achieves a statistically significant improvement in mental status over a period of 3 months when measured with BPRS, CGI and UKU scales. The response rate was 70 (45%) in the oral risperidone and 74 (28%) in the parenteral risperidone groups.Discussion: The addition of amisulpride could lead to an improvement in schizophrenia symptoms in patients that do not, or only partially, respond to risperidone. Further research is required into alternative therapies for poor responders.
Keywords: risperidone; amisulpride; augmentation; schizophrenia